Review: Glycerol Residue And Pitch Recovered From Oleo Chemical And Biodiesel Waste Industries - Nik Nor Aziati, Nik Abd Aziz; Mimi Sakinah, A. M.; Noraziah, Abu Yazid (2012)
The pretreatment process to recovered glycerol is a pretreatment method has been recognized as a method for environmental protection. This paper highlights the pretreatment methods to recovered the glycerol from two types and sources of glycerol waste i.e. glycerol residue from oleo chemical and glycerol pitch from biodiesel industries by pretreatment process. The purpose of this study is to explore the pretreatment potential use in glycerol waste pretreatment process. The general characterization of glycerol waste, application of glycerol waste recovered and pretreatment with operational parameters in terms pH, temperatures, ratio of solvent are thoroughly discussed in the paper. The data obtained and researchers discussed about the kinetic studies of the various pretreatments, thus giving maximum awareness about glycerol waste for further research. The future aspects for research needs are also outlined.